Developing L2 Pragmatics. (13th February 2013) - Bardovi‐Harlig, Kathleen
Abstract : This article positions research on the acquisition of pragmatics as an inquiry in the greater field of second language acquisition research. Viewing pragmatics from this intersection, I consider five areas of research that are of interest in both fields and have the potential to make significant contributions to second language pragmatics research. They are: the design and evaluation of pragmatics tasks as simulations of conversation; task design for the study of implicit and explicit knowledge; the measurement of pragmatic development; the interface of the development of grammar and lexicon with pragmatics; and the effect of environment on pragmatic development.